Sarcopenia and Menopause: The Role of Estradiol - Geraci, Annalisa; Calvani, Riccardo; Ferri, Evelyn; Marzetti, Emanuele; Arosio, Beatrice; Cesari, Matteo (Frontiers in Endocrinology, 2021)
During aging and menopausal transition in women, a progressive muscle degeneration (i.e. decrease in quality and muscle function) occurs. This muscle dysfunction, caused by decreased proliferation of muscle satellite cells, increased levels of inflammatory markers, and altered levels of sex hormones, exposes women to a raised incidence of sarcopenia. In this regard, hormonal balance and, in particular, estradiol seem to be essential in skeletal muscle function. The role of the estradiol on satellite cells and the release of inflammatory cytokines in menopausal women are reviewed. In particular, estradiol has a beneficial effect on skeletal muscle by stimulating satellite cell proliferation. Skeletal muscle can respond to estrogenic hormonal control due to the presence of specific receptors for estradiol at the level of muscle fibers. Additionally, estradiol can limit inflammatory stress damage on skeletal muscle. In this review, we primarily focused on the role of estradiol in sarcopenia and on the possibility of using Estradiol Replacement Therapy, which combined with nutritional and physical activity programs, can counteract this condition representing a valid tool to treat sarcopenia in women.